(untitled) (Jurnal Orthopaedagogia, 2025)
This study is motivated by the lack of awareness among autistic adolescents regarding sexual changes and behavior when entering puberty and the communication limitations of autistic adolescents. This puts adolescents with autism at risk of deviant sexual behavior or becoming victims of sexual violence. In schools, sex education is still not maximized because it is still a taboo in society, so the role of parents is very important in sex education. This study aims to describe the communication patterns of parents in providing sexual education to adolescents with autism in Surakarta. This study used a qualitative approach with a phenomenological method. The subjects in this study were four parents who have children with autism entering adolescence, selected through purposive sampling technique. Data collection techniques in this study include semi-structured interviews, observation, and documentation. The validity test used source and technique triangulation. The results of this study show that the communication pattern used by parents is a primary communication pattern with a linear communication model. Parents in delivering sexual education use simple instructions and contextual visual media adapted to the child’s understanding ability. The educational materials provided are adjusted to gender or sex, such as the use of sanitary napkins for girls and genital hygiene for boys. The conclusion of this study is that the communication pattern of parents in providing sexual education to adolescents with autism is a primary communication pattern, from the resulting pattern shows a communication model, namely a linear model.